2017
DOI: 10.1186/s12909-017-1074-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical examination in undergraduate medical education in the field of general practice – a scoping review

Abstract: Background: Physical examination (PE) is an essential clinical skill and a central part of a physician's daily activity. Teaching of PE has been integrated into medical school by many clinical disciplines with respective specific examination procedures. For instance, PE teaching in general practice may include a full-body examination approach. Studies show that PE-skills of medical students often need enhancement. The aim of this article was to scope the literature regarding the teaching and research of PE wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 85 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…The high level of diversification in the programs is consistent with previous studies that evaluated physical examination education for undergraduate medical students 29,30 . In addition, a review by Easton and colleagues found several medical models for teaching physical assessment in the published literature, but a general absence of evidence to support the superiority of one model over another 31 .…”
Section: Discussionsupporting
confidence: 81%
“…The high level of diversification in the programs is consistent with previous studies that evaluated physical examination education for undergraduate medical students 29,30 . In addition, a review by Easton and colleagues found several medical models for teaching physical assessment in the published literature, but a general absence of evidence to support the superiority of one model over another 31 .…”
Section: Discussionsupporting
confidence: 81%
“…As good communication skills are crucial for doctorpatient interactions, it is recommended to incorporate them in medical school programs from the very beginning [14,15]. Despite ongoing debate about the importance of improving medical students' and fully trained physicians' communication skills, structured communication skills (e.g., for the training of history-talking and teaching of physical examination [16]) are still underprovided in Germany [17][18][19][20][21][22]. Since introduction of the latest medical licensure act in Germany (2002), which requires training and examination of social, communications, and interpersonal skills in the teaching of prospective physicians, German medical faculties are faced with the challenges of implementing practical examinations and reducing the influence of written and oral exams [23,24].…”
Section: Communication Skills Of Medical Studentsmentioning
confidence: 99%
“…Mookherjee et al describe the state of PE instruction in graduate medical education (GME) [10] and Easton et al describe underlying educational theory in teaching PE skills in a narrative review [11]. Recently, Moßhammer et al published a scoping review describing how PE is taught in general practice [12]. However, a systematic review of the literature describing approaches to teaching PE skills to novice medical students is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…While Moßhammer et al describe teaching methodology in their review they did not describe the overall curriculum design in which these methodologies were used. Their scope also included interventions applied to learners at all phases of undergraduate medical education training [12].…”
Section: Introductionmentioning
confidence: 99%